Analisis Aplikasi Lembur Berbasis Web menggunakan System Usability Scale (SUS) Pada PT. XYZ - Ardi, Noper; Azhari, Dea Aprillia (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
In the digital era, efficient data management is crucial for companies as Information Technology facilitates staff tasks and operations. However, some companies still face challenges with manual data management, such as time-consuming and paper-based overtime request forms. PT XYZ still uses manual overtime forms and requires a more efficient system. Therefore, a Web-Based Overtime Application was developed using Laravel, PHP, and MySQL to streamline the entry and storage of employee data and overtime hours. The Waterfall method was used in the design process, encompassing requirements analysis, system design, implementation, testing, and maintenance, with data collected through interviews and observations. The research results indicate that this application improves company operations by automating the overtime request and approval process, and by facilitating the management and access to overtime data. Based on an average SUS score of 82, user acceptance falls within the